Hydraulic Conductivity Behaviors of Karst Aquifer With Conduit-Fissure Geomaterials - Li, Xian; Ke, Tingting; Wang, Yanqiao; Zhou, Tingguo; Li, Delong; Tong, Fang; Wen, Jinmei (Frontiers in Earth Science, 2020)
This study uses laboratory analog and numerical experiments to simulate groundwater flow in karst aquifer and investigate the dimension-dependent hydraulic conductivity for groundwater flow in conduit-fissure medium. A coupled Darcy-Navier-Stokes mathematical model were developed to simulate groundwater flow transmitting process in karst aquifer. The Darcy law was used to model the flow in the fissure and the Navier-Stokes equations were used for the flow in the conduit. A laboratory analog which simulate the conduit-fissure domains of a karst aquifer was used to provide verification of proposed mathematical models and the calibration of numerical simulations. Numerical simulations were adopted to solved the coupled Darcy-Navier-Stokes mathematical model. The numerical simulation results for flow match well with laboratory experimental results. Furthermore, the hydraulic conductivity for fully developed flow was identified as four control factors (conduit diameter, fracture aperture, hydraulic pressure and strata dip angle) by the numerical simulations. A new empirical equation was proposed to derive the hydraulic conductivity. The significance of each factor on the hydraulic conductivity was evaluated by statistical analysis. The evidence shows that the conduit diameter and fracture aperture have the most influence on the hydraulic conductivity.